App Imperialism: The Political Economy of the Canadian App Store. (June 2020) - Nieborg, David B.; Young, Chris J.; Joseph, Daniel
To critically engage with the political economy of platformization, this article builds on the concepts of platform capitalism and platform imperialism to situate platforms within wider historical, economic, and spatial trajectories. To investigate if platformization leads to the geographical redistribution of capital and power, we draw on the Canadian instance of Apple's iOS App Store as a case study. App stores are situated in a complex ecosystem of markets, infrastructures, and governance models that the disparate fields of business studies, critical political economy of communications, and platform studies have begun to catalog. Through a combination of financial and institutional analysis, we ask if Canadian game app developers are effective in generating revenue within their own national App Store. Given Canada's vibrant game industry one would expect Canadian developers to have a sizable economic footprint in the burgeoning app economy. Our results, however, point toward the US digital dominance and, therefore, we suggest the notion of app imperialism to signal the continuation, if not reinforcement of existing instances of economic inequalities and imperialism.